Pola Kepekaan E. coli Yang Diisolasi Dari Feses Burung Kicau Penderita Diare Terhadap Antibiotik Sulfametoksazol, Ampisilin, Dan Oksitetrasiklin (SENSITIVITY PATTERN OF E. coli ISOLATED FROM BIRD CHIRPING WITH DIARRHEA FECES AGAINST ANTIBIOTICS) - Handriana, I Kadek Juli; Suarjana, I Gusti Ketut; Gelgel, Ketut Tono Pasek (Buletin Veteriner Udayana; Vol. 7 No. 2 Agustus 2015, 2015)
This study aims were to determine the sensitivity pattern of Escherichia coli bacteria isolatedfrom the feces of birds chirping with diarrhea against antibiotic sulfamethoxazole, ampicillin, andoksitetrasiklin in Satria and Sanglah bird market.The results showed that all 30 isolates from birdfaeces were examined, sulfamethoxazole sensitive 3.3%, intermediate 13.3%, and resistant 83.3%.In oxytetracycline 3.3% sensitive, 40% intermediate, and 56.7% resistant . While sensitive to ampicillin 13.3%, 23.3% intermediate, and 63.3% resistant.
Keywords: birds chirping, E. coli, sulfametoksazol, ampicillin, oxytetracycline